Entangled core/shell magnetic structure driven by surface magnetic symmetry-breaking in Cr2O3 nanoparticles. Issue 5 (14th January 2022) - Rinaldi-Montes, Natalia; Gorria, Pedro; Fuertes, Antonio B.; Martínez-Blanco, David; Amghouz, Zakariae; Puente-Orench, Inés; Olivi, Luca; Herrero-Martín, Javier; Fernandez-Garcia, Maria Paz; Alonso, Javier; Phan, Manh-Huong; Srikanth, Hariharan; et al.
Abstract : The entangled core/shell magnetic structure of Cr2 O3 nanoparticles, where pinned uncompensated spins at the shell are randomly distributed in a low-temperature spin-glass ordering, gives rise to a Double Exchange-bias mechanism. Abstract : Bulk Cr2 O3 is an antiferromagnetic (AFM) oxide that exhibits the magnetoelectric effect at room temperature, with neither spontaneous magnetization nor net electric polarization. These physical properties stem from a subtle competition between exchange and crystal field interactions. In this article, we exploit the symmetry breaking at the surface of Cr2 O3 nanoparticles for unbalancing this delicate physical equilibrium. The emerging weak ferromagnetic signal we observe persists up to near room temperature (≈ 270 K) at which the antiferromagnetic order disappears. In addition, an exchange-bias effect, that rapidly decreases on heating from low temperature up to 30 K, is resistant to thermal disorder above 200 K. Our findings point to the possible formation of an entangled core/shell magnetic structure, where pinned uncompensated spins at the shell are randomly distributed in a low-temperature spin-glass ordering, with low net magnetic moment and an ordering temperature governed by the AFM Néel temperature.